Analysis of the Influence of Innovative Leadership, Product Development, and Marketing Strategy on Creative Industry Business Growth in Bandung - Judijanto, Loso; Suryadi, Irwan; Utami, Eva Yuniarti; Cahya, Darmawan Listya (Westscience Press, 2023)
This research investigates the intricate dynamics within the creative industry of Bandung City by analyzing the influence of Innovative Leadership, Product Development Strategies, and Marketing Strategies on Business Growth. A sample of 150 creative enterprises was surveyed, and structural equation modeling with partial least squares (SEM-PLS) was employed for quantitative analysis. The measurement model assessment confirmed the reliability and validity of the measurement instruments, while the structural model revealed significant positive relationships between the independent variables and Business Growth. Hypotheses testing supported the influence of Innovative Leadership, Product Development Strategies, and Marketing Strategies on Business Growth. The model fit indices indicated an acceptable fit, and the R-Square values suggested that approximately 60.2% of the variance in Business Growth can be explained by the combined influence of the studied factors. The regression results further confirmed the positive associations between each independent variable and Business Growth. The study contributes valuable insights for practitioners, policymakers, and researchers within the creative industry and concludes with recommendations for future research.